A crystallized exposition on Indian Muslims' attitude and consciousness towards halal. Issue 1 (6th March 2017) - Potluri, Rajasekhara Mouly; Ansari, Rizwana; Khan, Saqib Rasool; Dasaraju, Srinivasa Rao
Abstract : Purpose: This study aims to investigate the attitude and consciousness of Indian Muslims toward halal and also to indicate the alertness of Muslim students about halal in their daily life. Design/methodology/approach: A total of 500 respondents were selected for the study from the State of Andhra Pradesh in India, by stratified random sampling method; of which 300 were general Muslims and 200 were Muslim students. Self-administrated questionnaire and personal interviews were administered to garner the data, which were analyzed with SPSS (version 21.0) and GRETL, and the research hypotheses were tested with Z-test for proportion and Pearson's chi-square test. Findings: A total of 92 and 98 per cent of respondents from the general Muslim community and Muslim students, respectively, agreed that they do not have proper exposure to halal. In addition, 89 per cent of general Muslims believe that the halal concept is very significant to Muslim consumers as against 95 per cent students. A total of 98 and 96 per cent of the selected two classes of respondents, respectively, are intended to know more about halal. Research limitations/implications: The respondents in this research were general Muslims and Muslim students from Andhra Pradesh. The results of this research are, therefore, only applicable to the sampled community. Hence, generalization of the findings to the whole Indian Muslim population or to other areas of Muslim communities should be avoided. Practical implications: This research results proffer most precious and ingenious information to the corporate sector, Islamic religious organizations and educational institutions specially involved in formal Islamic education. Based on the snowballing trend of Muslim population from the present 250 million to the whopping 340 million by the end of this century, it is an inspired decision to target this lucrative segment which provide alluring profitability particularly food, cosmetics, medicines, etc., with Halal certified products. Specially, Islamic religious organizations also have an enormous onus to enhance the ken of this community on the matters comprehensively germane to Islam in general and about halal and haram in particular. Originality/value: This is the first ingenious effort aimed to investigate the attitude and awareness toward halal among general Muslims and Muslim students. This is a pioneering attempt on halal of Indian Muslims which is lucrative for both corporate sector and to the academia.